(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
Excavator teeth are critical components subjected to severe working conditions that lead to wear and corrosion, significantly impacting the performance and longevity of excavating equipment. This study investigates various methods to enhance the corrosion resistance of excavator teeth, focusing on material selection, surface treatments, and coating technologies. By improving corrosion resistance, we aim to extend the service life of excavator teeth, reduce maintenance costs, and enhance operational efficiency. The results indicate that advanced coating technologies, such as thermal spraying and laser cladding, combined with highperformance alloys, significantly improve corrosion resistance.